2018
DOI: 10.18832/kp201813
|View full text |Cite
|
Sign up to set email alerts
|

Brewing Microbiology - Bacteria of the Genera Bacillus, Brevibacillus and Paenibacillus and Cultivation Methods for their Detection - Part 1

Abstract: Bacteria of the genus Bacillus are often detected in brewing operations, but they rank among less hazardous contaminants. They are not able to survive in the vegetative form in beer and spoil it. Spores of Bacillus bacteria are present especially in malt and grain adjuncts. They are able to survive wort boiling, however in the following phases they are not able to germinate because of their sensitivity to bitter hop substances and low pH of fermenting wort and fi nished beer. We provide here an overview of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…S6). These two compounds are produced by various micro-organisms in the Bacillus and Lactobacillus genera respectively, both of which can attack and cause spoilage in food products such as dough, bread, and beer ( 27 29 ). Matches to these two compounds were only found in samples in which proteomics identified cereal and yeast proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6). These two compounds are produced by various micro-organisms in the Bacillus and Lactobacillus genera respectively, both of which can attack and cause spoilage in food products such as dough, bread, and beer ( 27 29 ). Matches to these two compounds were only found in samples in which proteomics identified cereal and yeast proteins.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, spectral matches for esperin and acidocin were found only in samples containing cereal and yeast proteins, from paintings A and D and paintings E and F, respectively. Esperin is an antibiotic produced by Bacillus mesentericus ( 63 ), a food contaminant also found in bread dough and beer ( 27 ). Acidocin is a bacteriocin produced by Lactobacillus acidophilus ( 29 ), one of the Lactobacillus species infamously known for infecting beer ( 64 ), but that can also be used to increase the beverage’s sourness ( 65 ) and in sourdough baking products ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spores of Bacillus bacteria are present especially in malt and grain adjuncts. They are able to survive wort boiling; however, in the following phases they are not able to germinate because of their sensitivity to bitter hop substances and low pH of fermenting wort and finished beer [28]. Some Bacillus species may cause food poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of genus Bacillus bacteria is inhibited especially by acid pH. However, some studies showed that Bacillus cereus could be able to survive and to grow for a certain period of time even at pH 4.2 -4.8 [39].…”
Section: General Characteristics Of Genus Bacillusmentioning
confidence: 99%